2016
DOI: 10.1080/21645515.2016.1242541
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of seasonal quadrivalent versus trivalent influenza vaccination in the United States: A dynamic transmission modeling approach

Abstract: Trivalent inactivated influenza vaccines (IIV3s) protect against 2 A strains and one B lineage; quadrivalent versions (IIV4s) protect against an additional B lineage. The objective was to assess projected health and economic outcomes associated with IIV4 versus IIV3 for preventing seasonal influenza in the US. A cost-effectiveness model was developed to interact with a dynamic transmission model. The transmission model tracked vaccination, influenza cases, infection-spreading interactions, and recovery over 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 46 publications
0
30
0
2
Order By: Relevance
“…The majority of the evaluated studies reported their outcomes using CUA [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Other types of economic evaluation considered were CEAs ( N = 11) [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], CBA (11 studies) [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ], or combining more than one type (10 studies) [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ,…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the evaluated studies reported their outcomes using CUA [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Other types of economic evaluation considered were CEAs ( N = 11) [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], CBA (11 studies) [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ], or combining more than one type (10 studies) [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ,…”
Section: Resultsmentioning
confidence: 99%
“…In order to prescribe vaccination, physician's knowledge should be regularly updated. [ 17 18 19 20 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…The taxonomy of modeling in economic evaluations of infectious diseases often varies among studies. Although several recent studies have used a static model (Chit et al, 2015;Clements et al, 2014), the use of a dynamic model for the economic evaluation of universal vaccination has increasingly gained attention (Baguelin et al, 2015;Baguelin et al, 2010;Brogan et al, 2016;Lugner et al, 2012;Meeyai et al, 2015;Pitman et al, 2013;Thommes et al, 2015). The static model is usually considered a conservative method and may be appropriately applied to interventions that are cost-effective.…”
Section: Discussionmentioning
confidence: 99%